Validation of the Portuguese Version of the Risk Instrument for Screening in the Community (RISC) Among Older Patients in Primary Care in Northern Portugal - Santos, Sara; O'Caoimh, Rónán; Teixeira, Laetitia; Alves, Sara; Molloy, William; Paúl, Constança (Frontiers in Public Health, 2021)
Background: Ageing is associated with an increase in adverse health outcomes for older people. Short screening instruments that easily and quickly identify those at highest risk can enable decision-makers to anticipate future needs, allocate scarce resources and act to minimize risk. The Risk Instrument for Screening in the Community (RISC) is a brief (2-5 minutes) Likert scale that scores one-year risk of institutionalization, hospitalization and death from low (1/5) to severe (5/5). Objectives: To externally validate the RISC, scored by general practitioners (GP´s), in primary care in Northern Portugal. Methods: The RISC was translated and culturally adapted to Portuguese. A cohort of 457 older adults (aged 65) under active follow-up with their GP´s were screened. Outcomes at one-year were recorded. Accuracy was determined from the area under the curve (AUC) of receiver operating curve analysis. Results: The mean age of participants was 75.2 years; 57% were female. The proportion identified as being at maximum risk (RISC scores of 3-5/5) of institutionalization, hospitalization and death, were 14.9%, 52.4% and 38.4%, respectively. At follow-up 2% (10/431) were institutionalized, 18.6% (84/451) were hospitalized and 3% (14/456) died. Those who were institutionalised (p=0.021), hospitalised (p=0.012) or dead (p<0.001) at one-year were significantly older. Those living alone were more likely to be institutionalised (p=0.007). The RISC showed fair accuracy in predicting hospitalization (AUC of 0.62 [95% CI:0.55-0.69]) and good accuracy for Institutionalization (AUC of 0.79 [95% CI:0.62-0.96]) and death (AUC of 0.77 [95% CI:0.65-0.88]). Conclusions: The Portuguese version of the RISC accurately predicted institutionalisation and death at one-year but like most short screens was less able to predict hospitalisation. Given its brevity, the RISC is useful for quickly identifying and stratifying those at increased risk in primary care.